i-PRESTIGE : 2023 Annual report research, Industrial Linkages and Alumni Division UiTM Cawangan Johor. - Misman, Faridah Najuna; Mokhtar, Nurkhairany Amyra; Mazan, Diana'; Shaari, Nur Fatihah; Mat Kamal, Siti Nuur-Ila; Majid, Muhammad; Mohamad Khalid, Rusnani; Md Isa @ Kamarudin, Maizura; Abd Aziz, Noreen Noor; Abdol Rahim @ Ibrahim, Abdul Hadi; Ng, Set Foong; Rusli, Ahmad Najmie; et al. (Research, Industrial Linkages and Alumni Division, 2023)
In the name of Allah, the most Gracious and the most Merciful. May he grant blessings and peace to Prophet Muhammad (S.A.W) and his family. It is with immense pride and pleasure that I welcome you to this edition of Intellectual Prestige (i-PRESTIGE) for the year of 2023. i-PRESTIGE 2023 is a compilation and publication of reports from the different units under the Research, Industry Linkages and Alumni Division (PJI&A) of UiTMCJ. This publication stands as a testament to the vibrant intellectual and creative spirit that thrives within our university community. Each edition captures the essence of our collective achievements, the dynamic pursuits of our students, faculty, and staff, and the innovative research and projects that define our institution. I would also like to extend my deepest gratitude to the PJI&A team for their hard work and dedication. Their meticulous efforts in curating and presenting the diverse content within these pages are truly commendable. Their utmost commitment to quality has brought this edition to life, creating a publication that we can all be proud of. As you delve into this edition of i-PRESTIGE 2023, I hope you find inspiration in the achievements shared within to generate more ideas and interests, and spark greater motivations, in the academia and upon other staffs, for a more successful and productive year, 2024. Let these pages remind us of the extraordinary potential that lies within our university community and the shared commitment to excellence that unites us all. Thank you for your continuous support and engagement with UiTM Cawangan Johor. Together, we will continue to foster an environment of learning, discovery, and innovation.